Impact of stoniness correction of soil hydraulic parameters on water balance simulations of forest plots. Issue 1 (24th November 2016) - Wegehenkel, Martin; Wagner, Annette; Amoriello, Tiziana; Fleck, Stefan; Meesenburg, Henning; Raspe, Stephan
Abstract: Long‐term estimates of the water balance of forests are essential for forest ecosystem analysis. Such estimates can be achieved by using numerical modelling approaches for water balance calculations. These modelling approaches require data, e.g ., for the description of the hydraulic properties of forest soils using soil water retention or hydraulic conductivity functions. However, these functions are usually valid only for fine‐earth conditions. However, many forest soils, especially those located in mountainous regions, contain larger fractions of gravel and rock fragments in the soil profiles. In our study, the impact of stoniness correction of soil hydraulic functions on the performance of a numerical water balance modelling approach was evaluated by using continuously measured time series of daily throughfall, soil water contents and pressure heads provided from three different ICP Forests Level II plots with high stoniness in the soil profiles. These measured data were compared with the corresponding model outputs. The application of stoniness correction of the soil hydraulic functions improved the model performance in terms of the Nash‐Sutcliffe Index NS and the coefficient of determination R 2 . This indicated the need for such a correction.